Job Demand Verses Burnout at Bank Rakyat / Siti Amirah Sudiman - Sudiman, Siti Amirah (Universiti Teknologi MARA Sarawak,Kampus Samarahan, 2015)
Primarily this research will be used to study the relationship between the jobs demand and burnout that will be face by the employees of Bank Rakyat. The dependent variable for this study is stress and the independent variable for it is the workloads. Furthermore, the banking industry is well known as one of the industry that has busy working environment and the employees are exposed to work's burnout that may also affect their daily life style. Besides, the research may also help to find the solution for the problems by identify the causes of burnout and researcher will have the chance to solve the problems or may also try to avoid the problem from happening.